(untitled) (Avocetta, 2019)
“Black-tyrants” (Tyrannidae: Knipolegus) are a distinctive Neotropical genus of flycatchers with black or dark grey males and brownish or reddish females. Five species have previously been reported in Paraguay and a discussion of all verifiable reports is provided. Knipolegus striaticeps is considered resident and a presumed breeder, but no nest has yet been reported. Knipolegus hudsoni is considered a passage migrant in September and October. Knipolegus cyanirostris is considered a winter visitor. Knipolegus aterrimus is known from few records in the Chaco region, and is possibly a rare altitudinal migrant. The status of Knipolegus lophotes requires further investigation, with Paraguay representing the western extreme of its known range. The first report of Knipolegus poecilurus for the country is documented with photographs. This high-Andean species is considered to be a vagrant pending further information.